Prognostic Value of Relative Adrenal Insufficiency During Cardiogenic Shock: A Prospective Cohort Study With Long-Term Follow-Up. Issue 1 (January 2017) - Bagate, François; Lellouche, Nicolas; Lim, Pascal; Moutereau, Stephane; Razazi, Keyvan; Carteaux, Guillaume; de Prost, Nicolas; Dubois-Randé, Jean-Luc; Brun-Buisson, Christian; Mekontso Dessap, Armand
ABSTRACT: Background: Relative adrenal insufficiency (RAI) is common in intensive care unit patients, particularly during septic shock (SS). Cardiogenic shock (CS) may share some pathophysiological features with SS. The aim of this study was to evaluate the prevalence and long-term prognosis of RAI during CS. Patients and Methods: Prospective observational study conducted in the intensive care and cardiology units in one university hospital in France. Patients meeting the criteria for CS without prior corticosteroid therapy were included. Total blood cortisol levels were assessed immediately before (T0) a short corticotropin stimulation test (0.25 mg i.v. of tetracosactrin) and 30 and 60 min afterward. Δmax was defined as the difference between the maximal value after the test and T0. Results: Of the 92 patients enrolled, 42 (46%) (95% confidence interval [CI] [36%–56%]) died in hospital and 7 more died during a median follow-up of 616 [57–2, 498] days, for an overall mortality rate of 53% (95% CI [43%–63%]). Three groups were identified based on the corticotropin test: group 1 (T0 ⩽798 nmol/L and Δmax >473 nmol/L), group 2 ([T0 >798 nmol/L and Δmax >473 nmol/L] or [T0 ⩽798 nmol/L and Δmax ⩽473 nmol/L]), and group 3 (T0 >798 nmol/L and Δmax ⩽473 nmol/L) with an overall survival of 76%, 43%, and 15%, respectively (log rank P  = 0.003). In the multivariable analysis, adrenal nonresponse (group 3) was an independent predictor of mortality ( P  = 0.04), along with left ventricular ejection fraction, Simplified Acute Physiology Score II, and cardiac arrest. Conclusions: These data suggest that a short corticotropin test has a good prognostic value in CS and allows identifying patients at higher risk of death. Abstract : Supplemental Digital Content is available in the text